2020
DOI: 10.1093/cid/ciaa435
|View full text |Cite
|
Sign up to set email alerts
|

Regional Emergence ofCandida aurisin Chicago and Lessons Learned From Intensive Follow-up at 1 Ventilator-Capable Skilled Nursing Facility

Abstract: Background Since the identification of the first 2 Candida auris cases in Chicago, Illinois, in 2016, ongoing spread has been documented in the Chicago area. We describe C. auris emergence in high-acuity, long-term healthcare facilities and present a case study of public health response to C. auris and carbapenemase-producing organisms (CPOs) at one ventilator-capable skilled nursing facility (vSNF-A). Methods We performed po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 20 publications
1
77
0
Order By: Relevance
“…Previously, a contact tracing and epidemiologic investigation surrounding cases earlier in the C. auris epidemic in New York revealed that colonisation rates varied by facility type, i.e., hospitals (5%), long term care facilities (LTCF, 6.3%), long term acute care (2.9%), and co-located hospital and LTCF (12.3%) [ 38 ]. C. auris colonisation rates in skilled nursing facilities that cared for ventilated patients were nearly ten times higher than the prevalence in skilled nursing facilities that did not provide care for ventilated residents [ 38 , 39 ]. It is pertinent to emphasize that colonisation by C. auris predisposes patients at risk for invasive infection as 5–10% of known colonised patients have been reported to develop invasive infections [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a contact tracing and epidemiologic investigation surrounding cases earlier in the C. auris epidemic in New York revealed that colonisation rates varied by facility type, i.e., hospitals (5%), long term care facilities (LTCF, 6.3%), long term acute care (2.9%), and co-located hospital and LTCF (12.3%) [ 38 ]. C. auris colonisation rates in skilled nursing facilities that cared for ventilated patients were nearly ten times higher than the prevalence in skilled nursing facilities that did not provide care for ventilated residents [ 38 , 39 ]. It is pertinent to emphasize that colonisation by C. auris predisposes patients at risk for invasive infection as 5–10% of known colonised patients have been reported to develop invasive infections [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…During this period cases reached Australia (2015) as well [49]. Around the same time when cases emerged in the UK, C. auris had entered the USA (2013) as well [50], and it triggered prolonged large outbreaks in New York, New Jersey and Chicago over 2013–17 [8, 51]. Soon after, in 2017, C. auris cases emerged in Canada [52].…”
Section: Emergence and Global Spreadmentioning
confidence: 99%
“…Second, patients in vSNFs generally have long lengths of stay — often much longer than patient stays at LTACHs [66] — meaning that they have a longer period of time to acquire a multi-drug resistant organism. Furthermore, multibed rooms are common and the facilities themselves are often under-resourced from a staffing and infection control perspective [6], both of which could facilitate intra-facility spread. Our findings paired with these observations indicate that vSNFs may be important healthcare facilities to detect emerging threats and potentially contain them before widespread dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term acute care hospitals (LTACHs) and ventilator-capable skilled nursing facilities (vSNFs) are potentially high-impact settings for implementation of regional CRE surveillance and infection prevention interventions [5,6]. Patients in these facilities have been shown to be colonized with CRE at high rates, likely due to a combination of their chronic severe illness, long lengths of stay, and high rates of prior or on-going antibiotic exposure.…”
Section: Introductionmentioning
confidence: 99%